2006
DOI: 10.1124/mol.106.028688
|View full text |Cite
|
Sign up to set email alerts
|

A 46-Amino Acid Segment in Phosphodiesterase-5 GAF-B Domain Provides for High Vardenafil Potency over Sildenafil and Tadalafil and Is Involved in Phosphodiesterase-5 Dimerization

Abstract: Phosphodiesterase-5 (PDE5) contains a catalytic domain (C domain) that hydrolyzes cGMP and a regulatory domain (R domain) that contains two mammalian cGMP-binding phosphodiesterase, Anabaena adenylyl cyclases, Escherichia coli FhlAs (GAFs) (A and B) and a phosphorylation site for cyclic nucleotide-dependent protein kinases (cNPKs). Binding of cGMP to GAF-A increases cNPK phosphorylation of PDE5 and improves catalytic site affinity for cGMP or inhibitors. GAF-B contributes to dimerization of PDE5, inhibition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 38 publications
3
33
0
Order By: Relevance
“…All constructs were confirmed by DNA sequencing before cotransfection with BaculoGold linear baculovirus DNA (BD Biosciences PharMingen) according to the protocol from BD Biosciences PharMingen. Proteins were expressed in Sf9 cells, purified to near homogeneity using Ni 2ϩ -NTA resin and characterized as described previously (Blount et al, 2006). Constructs were flash frozen in Tris buffer (20 mM Tris, pH 8, and 50 mM NaCl) containing a final concentration of 20% glycerol.…”
Section: Conversion Of Pde5 By Inhibitors 731mentioning
confidence: 99%
See 1 more Smart Citation
“…All constructs were confirmed by DNA sequencing before cotransfection with BaculoGold linear baculovirus DNA (BD Biosciences PharMingen) according to the protocol from BD Biosciences PharMingen. Proteins were expressed in Sf9 cells, purified to near homogeneity using Ni 2ϩ -NTA resin and characterized as described previously (Blount et al, 2006). Constructs were flash frozen in Tris buffer (20 mM Tris, pH 8, and 50 mM NaCl) containing a final concentration of 20% glycerol.…”
Section: Conversion Of Pde5 By Inhibitors 731mentioning
confidence: 99%
“…The R domain contains several functional subdomains, including a phosphorylation site (Ser-102 in hPDE5), allosteric cGMP binding sites, and dimerization contacts (Thomas et al, 1992;McAllister-Lucas et al, 1995;Zoraghi et al, 2005;Blount et al, 2006). Binding of inhibitors such as 3-isobutyl-1-methylxanthine or sildenafil to the PDE5 catalytic site increases affinity of the allosteric site in the R domain for cGMP (Francis et al, 1980;Corbin and Francis, 1999).…”
mentioning
confidence: 99%
“…It has been demonstrated using solution biochemistry that many of the kinetic characteristics of an isolated C domain can be quite similar to those of the holoenzyme (Fink et al, 1999;Wang et al, 2006;Weeks et al, 2007). However, other characteristics of PDE holoenzymes can influence contacts and potency of certain inhibitors (e.g., dimerization, phosphorylation, or additional structural features) (Richter and Conti, 2004;Blount et al, 2006). Because these earlier reports demonstrated that significant structural differences can exist between a PDE holoenzyme and its isolated C domain in solution, it seems equally plausible that contacts defined from an X-ray crystal structure of an isolated C domain and certain ligands may not precisely recapitulate those that occur in the holoenzyme.…”
Section: Pde11 Invariant Glutamine and Ligand Binding 137mentioning
confidence: 99%
“…Because these earlier reports demonstrated that significant structural differences can exist between a PDE holoenzyme and its isolated C domain in solution, it seems equally plausible that contacts defined from an X-ray crystal structure of an isolated C domain and certain ligands may not precisely recapitulate those that occur in the holoenzyme. Thus, for development of the most accurate insights into the biochemical properties of interaction between PDEs and ligands, it is important to compare results derived from biochemical studies of PDE11 holoenzyme in solution with insights and predictions derived from X-ray crystal structures of other PDEs (Sung et al, 2003;Zhang et al, 2004;Blount et al, 2006).…”
Section: Pde11 Invariant Glutamine and Ligand Binding 137mentioning
confidence: 99%
See 1 more Smart Citation